PRONOUNS (Modern education and development, 2025)
Pronouns are an essential part of grammar, playing a key role in facilitating the smooth functioning of language. They replace nouns to avoid repetition and make sentences more concise and coherent. This article provides detailed information about the different types of pronouns, their functions, and how they are used in both written and spoken language.